Pengaruh Kualitas Pelayanan Bank BNI Terhadap Kepuasan Mahasiswa Sebagai Nasabah di UNIMED - Hotman Siboro; Nurita Pasaribu; Syaqinah Ujung; Hasyim Hasyim (Journal on Education, 2024)
This research explores the impact of service quality at Bank Negara Indonesia on student satisfaction as customers at Universitas Negeri Medan. In the context of intense competition within the banking sector, service quality has become a key factor in attracting and retaining customers. Utilizing a quantitative approach, this study employs surveys to collect data from students who are customers of BNI. The analysis results indicate a significant positive influence between service quality and customer satisfaction. Each improvement in service quality contributes to an increase in student satisfaction. These findings emphasize the importance of BNI in enhancing service quality dimensions, such as responsiveness and attention to customers, to meet the expectations of the younger generation. By understanding these factors, BNI is expected to strengthen customer loyalty and enhance competitiveness in the banking industry. This research provides valuable insights for bank management in formulating more effective service strategies.